Analisis Penerapan Peraturan Daerah Nomor 6 Tahun 2017 Tentang Retribusi Pajak Daerah - Kalay, Lisman; Ahmad, Ibrahim; Ismail, Nurwita (CV. Era Digital Nusantara, 2024)
The purpose of this study is to find out the application of Regional Regulation Number 6 of 2017 Concerning Retribution for General Services in Gorontalo Regency. To find out what factors cause the implementation of Regional Regulation Number 6 of 2017 concerning General Service levies in Gorontalo Regency. In this research the author uses Empirical research method. The data sources used in this research are primary and secondary data. The author uses direct observation and interview data collection techniques. In this research, the author analyzes data using quantitative methods, namely analyzing data and providing relevant explanations, the problem is discussed further research and analysis is carried out and makes a conclusion. The implementation of Regional Regulation Number 6 of 2017 concerning Regional General Service Retribution in Gorontalo Regency has regulated how the retribution mechanism, but in its application it has not been effective, basically the potential of regional retribution in Gorontalo Regency can have a good impact on regional development, regional retribution whose revenue potential is classified as excellent. The constraints in local retribution revenue in Gorontalo Regency consist of several things, namely, influenced by three factors including substance, structure and culture. Human resources in quality and quantity are still lacking, inadequate facilities, lack of supervision, the application of sanctions that have not been maximized, lack of awareness of mandatory retribution, lack of coordination and lack of socialization.